2011
DOI: 10.1007/s11250-011-9954-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for intestinal parasite infection in goats raised in Nakhon Pathom Province, Thailand

Abstract: The objectives of this study were to determine the prevalence and risk factors for intestinal parasite infection in goats raised in Nakhon Pathom Province. Fecal samples from 190 goats in 12 herds were collected per rectum. Questionnaires focusing on the general information about the farm and farmers, and management practices on farms were completed. Modified McMaster counting technique was performed to detect eggs of intestinal parasites. Each egg found was classified into three groups of parasites based on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 24 publications
(33 reference statements)
5
23
0
2
Order By: Relevance
“…The data showed less variability for cattle (150) than goats (875). Even with different breeding (Caninde, Bhuj and Anglo-Nubian) values can be higher for goats, but not for cattle, as shown in other studies: Costa et al (2000) with a mean EPG varying from 302 to 397 (lower than our average of 1,728 EPG), and other studies in goats conducted in Thailand and Bangladesh, with averages of 1,176 and 263 EPG, respectively (RATANAPOB et al, 2012;HASSAN et al, 2011). Our results were higher than other studies with periparturient animals, such as that of Sweeny et al (2011), where a high worm egg count in Dorper lambs was associated with a lower body condition score.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The data showed less variability for cattle (150) than goats (875). Even with different breeding (Caninde, Bhuj and Anglo-Nubian) values can be higher for goats, but not for cattle, as shown in other studies: Costa et al (2000) with a mean EPG varying from 302 to 397 (lower than our average of 1,728 EPG), and other studies in goats conducted in Thailand and Bangladesh, with averages of 1,176 and 263 EPG, respectively (RATANAPOB et al, 2012;HASSAN et al, 2011). Our results were higher than other studies with periparturient animals, such as that of Sweeny et al (2011), where a high worm egg count in Dorper lambs was associated with a lower body condition score.…”
Section: Resultssupporting
confidence: 67%
“…Although intestinal parasite infections in production animals are a well-known problem, there are still very few studies on this matter in Thailand (RATANAPOB et al, 2012) and in other countries in Southeast Asia, such as Lao PDR. The study area was located in Ban Lahanam, Savannakhet Province, a southern region of Lao PDR.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to the availability of a wide grazing area within the source location of the host animal, which increased the chance of picking up cysts, ova, larvae or intermediate hosts of these GI helminths in the pastures. In addition, temperature, humidity and rainfall in the grazing area and the grazing behavior of these hosts are also highly favorable for parasite transmission [9,42]. Moreover, susceptibility to infections is influenced by various factors like age, species, health status and previous exposure to parasites [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of a parasitic infection varies greatly by area, depending on many factors such as level of agriculture, pasture management, micro-and macro-climate of the environment, immunological and nutritional status of the host, presence of intermediate hosts, vectors, and the numbers of infecting larvae and eggs in the environment [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, coccidiosis caused by genus the Eimeria is one of widely spread parasitic diseases either clinically or subclinically among small ruminants in Egypt and all over the world (Agyei et al 2004;Gadelhaq et al, 2015;Majeed et al 2015). Coccidian parasites contribute to enteric disease particularly in young or goats under stress in poor farm conditions, which lead to high mortality rate among goat kids (Ratanapob et al 2012). Several studies revealed that Balantidium coli (B. coli) and Entamoeba spp.…”
Section: Introductionmentioning
confidence: 99%